Assessment of the Kempe Family Stress Inventory in self-care post-restrain schizophrenia - Ah Yusuf; Muhammad Suhron; Rika Subarniati (International Journal of Public Health Science (IJPHS), 2019)
Basic Health Research stated that the prevalence of schizophrenia in the Indonesian population in 2018 showed schizophrenia was seven per mile; previously only 1.7 permil. The aim of the study was to explain the stress reaction and experience of families who have people with schizophrenia post-restrain. The Methods A total of 135 families who have people with schizophrenia post-restrain October to December 2018. This research was Mix Method employed Sequential Explanatory design. the research instrument used was The Kempe Family Stress Inventory (KFSI) and using in-depth interview. The results of the study illustrated that the total mean score of a stress reaction in families normal was 43.48 (S.D=5.6),mild was 34.33 (S.D=4.7) whilesevere was 56.45 (S.D=4.45). The psychological burden was expressed by families in the form of fear and worry. The results showed a reaction to high stress and family experience lacking in self-care of people with post-restrain mental disorders.